HOUSEHOLD FINANCES AND SUBJECTIVE FINANCIAL WELL-BEING IN INDONESIA - Amatul Ghina, Aisyah
This study assesses the impact of household financial position and social comparison on individual’s subjective financial well-being (FWB) in Indonesia. Using the latest wave of Indonesia Family Life Survey (IFLS) dataset, we measure subjective FWB based on questions on subjective prosperity, perceived current standard of living adequacy and perceived future standard of living. The empirical analysis shows that net wealth and total assets are also essential determinants and positively related to FWB along with income. On the contrary, though it is only found significant on the perceived current standard of living adequacy, the total debt level has a negative effect on FWB. The findings also confirm that socioeconomic and demographic factors also significantly affect FWB (e.g., being female and more educated has a positive effect on FWB). Furthermore, we also found that relative financial position (i.e., social comparison) has important roles in determining individuals' FWB level. Being above the reference group's average for a particular financial measure (i.e., income and total assets) has a positive effect on an individual's FWB. Our study contributes to the growing literature on financial well-being in a developing country, particularly in Indonesia.